The Intersections of COVID-19 Global Health Governance and Population Health Priorities: Equity-Related Lessons Learned From Canada and Selected G20 Countries - Muriel Mac-Seing; Muriel Mac-Seing; Erica Di Ruggiero; Erica Di Ruggiero; Erica Di Ruggiero (Frontiers Media S.A., 2024)
Background: COVID-19-related global health governance (GHG) processes and public health measures taken influenced population health priorities worldwide. We investigated the intersection between COVID-19-related GHG and how it redefined population health priorities in Canada and other G20 countries. We analysed a Canada-related multilevel qualitative study and a scoping review of selected G20 countries. Findings show the importance of linking equity considerations to funding and accountability when responding to COVID-19. Nationalism and limited coordination among governance actors contributed to fragmented COVID-19 public health responses. COVID-19-related consequences were not systematically negative, but when they were, they affected more population groups living and working in conditions of vulnerability and marginalisation.Policy options and recommendations: Six policy options are proposed addressing upstream determinants of health, such as providing sufficient funding for equitable and accountable global and public health outcomes and implementing gender-focused policies to reduce COVID-19 response-related inequities and negative consequences downstream. Specific programmatic (e.g., assessing the needs of the community early) and research recommendations are also suggested to redress identified gaps.Conclusion: Despite the consequences of the COVID-19 pandemic, programmatic and research opportunities along with concrete policy options must be mobilised and implemented without further delay. We collectively share the duty to act upon global health justice.